2008
DOI: 10.1590/s0100-204x2008000900017
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade de agregados e distribuição de carbono e nutrientes em Argissolo sob adubação orgânica e mineral

Abstract: Resumo -O objetivo deste trabalho foi avaliar o impacto da adubação orgânica e mineral sobre a estabilidade de agregados e a distribuição de C, N e P, em classes de agregados de um Argissolo Vermelho-Amarelo. Os tratamentos consistiram de 0 e 40 m 3 ha -1 por ano de adubação orgânica e de 0, 250 e 500 kg ha -1 de adubação mineral N-P-K da fórmula 4-14-8. Uma área sob floresta atlântica foi utilizada como referência. Amostras foram coletadas nas camadas de 0-10 e 10-20 cm. Houve predomínio da classe de agregado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
19

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
3
7
0
19
Order By: Relevance
“…In this study, the response of carbon and nitrogen contents to different UWC rates was similar, since, regardless of the treatment, the C:N ratio (11:1) was constant ( Table 5). These results agree with those of Matos et al (2008), who observed an increase in carbon stocks and soil aggregate stability from the application of organic fertilizer. Rozane et al (2010) evaluating the effect of management systems on aggregate stability, observed that GMD and MWD were higher in the 0.0-0.10 m layer, related to the increase in SOC content.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the response of carbon and nitrogen contents to different UWC rates was similar, since, regardless of the treatment, the C:N ratio (11:1) was constant ( Table 5). These results agree with those of Matos et al (2008), who observed an increase in carbon stocks and soil aggregate stability from the application of organic fertilizer. Rozane et al (2010) evaluating the effect of management systems on aggregate stability, observed that GMD and MWD were higher in the 0.0-0.10 m layer, related to the increase in SOC content.…”
Section: Resultssupporting
confidence: 92%
“…In the 2009/ 10 growing season, results were similar for both GMD and MWD (Figure 1), with a linear increase in the quantity of aggregates retained in the sieve class 8.00-4.76 mm, indicating that aggregate stability increases with UWC application on the soil. This may be related to greater root growth and the contribution of organic matter, as also reported by Matos et al (2008).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations